Emergency Management of Epilepsy and Seizures - Bank, Anna M.; Bazil, Carl W. (Seminars in Neurology, 2019)
Seizure- and epilepsy-related complications are a common cause of emergency medical evaluation, accounting for 5% of 911 calls and 1% of emergency department visits. Emergency physicians and neurologists must be able to recognize and treat seizure- and epilepsy-related emergencies. This review describes the emergency evaluation and management of new onset seizures, breakthrough seizures in patients with known epilepsy, status epilepticus, acute symptomatic seizures, and acute adverse effects of antiepileptic drugs.
Keywords: new onset seizures; breakthrough seizures; status epilepticus; antiepileptic drug toxicity